COVID-19 PANDEMIC PERIOD IN THE DISTANCE EDUCATION PROCESS PHYSICAL EDUCATION TEACHERS PROBLEMS AND SUGGESTIONS - NALAN AKSAKAL; Serdar Kocaekşi; Mert Erkan; Türkan Nihan Sabırlı; Ahmet Coşkun (International Journal of Eurasia Social Sciences, 2024)
The aim of this study is to identify the problems and suggestions faced by physical education teachers during the distance education process during the Covid-19 pandemic period. In this study, which was conducted with a phenomenological design, one of the qualitative research methods, 13 physical education teachers participated by using chain sampling method, one of the purposeful sampling methods. The data were collected through semi-structured interview technique and the data obtained were analyzed by content analysis. According to the findings obtained in the research; the themes of problems experienced in physical education courses in the distance education process, physical education course processing in the distance education process and solution suggestions for the functioning of the physical education course in the distance education process were reached. As a result, considering the problems experienced by physical education teachers in the distance education process, it was concluded that the process of conducting the physical education course with distance education could not be carried out successfully, and for a more qualified distance education application, both the technological infrastructure system should be developed, the curriculum should be structured according to the distance education processes, and trainings should be organized to ensure that students, teachers and parents who use the system have sufficient knowledge.